Natural Deep Eutectic Solvents as Sustainable Solvents for Suzuki–Miyaura Cross-Coupling Reactions Applied to Imidazo-Fused Heterocycles - Delaye, Pierre-Olivier; Pénichon, Mélanie; Boudesocque-Delaye, Leslie; Enguehard-Gueiffier, Cécile; Gueiffier, Alain (SynOpen, 2018)
Herein, we present the first Suzuki–Miyaura cross-coupling in a sustainable natural deep eutectic solvent (NaDES) applied to biologically relevant imidazo-fused scaffolds imidazo[1,2-a]pyridine and imidazo[1,2-b]pyridazine. The choline chloride/glycerol (1:2, mol/mol) NaDES allowed the functionalisation of diverse positions on the heterocycles with various boronic acids, by using 2.5 mol% of readily available Pd(OAc)2. Notably, the catalytic system proceeds without any ligands or additives, without protection from the atmosphere.
Keywords: deep eutectic solvent; imidazopyridine; Suzuki–Miyaura coupling; sustainable chemistry